An examination of potential biases in research designs used to assess the efficacy of sex offender treatment. Issue 4 (12th October 2015) - Beech, Anthony; Freemantle, Nick; Power, Caroline; Fisher, Dawn
Abstract : Purpose: – The purpose of this paper is to examine the potential biases in research designs used to assess the efficacy of sex offender treatment. Design/methodology/approach: – In all, 50 treatment studies ( n =13, 886) were examined using a random effects meta-analysis model. Findings: – Results indicated a positive effect of treatment for both sexual (OR=0.58, 95%, CI 0.45-0.74, p < 0.0001), and general recidivism (OR=0.54, 95%, CI 0.42-0.69, p < 0.0001), indicating that the likelihood of being reconvicted after treatment was around half compared to no treatment. RCTs showed no significant effect for sexual or general, recidivism. Significant effects were found for non-RCT designs (i.e. incidental cohort, completers vs non-completers designs). Assignment based on need (i.e. giving treatment to those who were high-risk) indicated a negative effect of treatment. Practical implications: – The results highlight the importance of considering study design when considering treatment efficacy. Originality/value: – The current research reports studies identified up until 2009, and examined both published, and unpublished, research originating from a variety of samples employing a random effects model. Consequently, it can be argued that the results are both original and are reflective not only of identified studies, but are also representative of a random set of observations drawn from the common population distribution (Fleiss, 1993). The results of the study suggest that what is required in future research is methodological rigour, and consistency, in the way in which researchers measure the effectiveness of sexual offender treatment.